Quantitative determination of adenovirus-mediated gene delivery to rat cardiac myocytes in vitro and in vivo. - Kass-Eisler, A (1993)
To optimize the use of modified adenoviruses as vectors for gene delivery to the myocardium, we have characterized infection of cultured fetal and adult rat cardiac myocytes in vitro and of adult cardiac myocytes in vivo by using a replication-defective adenovirus carrying the chloramphenicol acetyltransferase (CAT) reporter gene driven by the cytomegalovirus promoter (AdCMVCATgD). In vitro, virtually all fetal or adult cardiocytes express the CAT gene when infected with 1 plaque-forming unit of virus per cell. CAT enzymatic activity can be detected in these cells as early as 4 hr after infection, reaching near-maximal levels at 48 hr. In fetal cells, CAT expression was maintained without a loss in activity for at least 1 week. Using in vitro studies as a guide, we introduced the AdCMVCATgD virus directly into adult rat myocardium and compared the expression results obtained from virus injection with those obtained by direct injection of pAdCMVCATgD plasmid DNA. The amount of CAT activity resulting from adenovirus infection of the myocardium was orders of magnitude higher than that seen from DNA injection and was proportional to the amount of input virus. Immunostaining for CAT protein in cardiac tissue sections following adenovirus injection demonstrated large numbers of positive cells, reaching nearly 100% of the myocytes in many regions of the heart. Expression of genes introduced by adenovirus peaked at 5 days but was still detectable 55 days following infection. Adenoviruses are therefore a very useful tool for high-efficiency gene transfer into the cardiovascular system.